Pengaruh Faktor Sosial Budaya, Partisipasi Masyarakat, Dan Faktor Kebijakan Anggaran Pemerintah Daerah Terhadap Lompatan Penurunan Kematian Bayi Di Kabupaten Ngada Dan Kupang - Margarteha Ulemadja Maria Wedho (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
The infant mortality rate (IMR) in East Nusa Tenggara Province is still high, with the number of deaths from 2011-2014 fluctuating between 1219-1350 cases. The purpose of this study was to determine the influence of factors of community participation, socio-cultural, and regional government budget policies on reducing infant mortality rates in Ngada and Kupang districts. The type of research used is qualitative with the support of quantitative data. The population in the study were all managers of Maternal and Child Health from the district level (government, health office) to the village level. Purposive non-random sampling is used to obtain a sample consisting of the district level: the head of the financial planner, the head of the maternal and child health department of the health department. The Puskemas is the head of the Puskemas and is in charge of Maternal and Child Health. The sub-district level is the head of the health affairs section; village level is the village head, 4 Neighborhood heads / Head of Hamlets/community leaders, and 4 cadres. In terms of recipients of health services are 4 mothers after childbirth and husband. The results showed that the socio-cultural factors of the community, both sex, occupation, and low level of education, as well as customs in Kupang Regency, greatly influenced the pattern of handling newborns. Plus the low participation of village government resulted in high mortality rates compared to other districts, especially Ngada. Community participation in this case during the pregnancy period in both districts was still low which affected delays in making decisions. Regional government budgetary independence in Ngada and Kupang districts is still lacking in accelerating the program to reduce infant mortality. The recommendations given are that the health department is expected to focus more on training to reduce the causes of newborn deaths such as the handling of infants with Asphyxia, Acute Respiratory Distress Syndrome, Infection for nurses/midwives; and cadres and community leaders.